ASSESSING ADDED VALUE OF COOPERATION BETWEEN CORPORATE GROUP WITH ITS CORPORATE VENTURE CAPITALâS PORTFOLIO (CASE STUDY OF PT.X) - Pawestri, Ayunindya
As technology growing rapidly, the disruptive innovation will be a threat for incumbents through its new business model which involve technology. As a preparation to enter this era, digital transformation is required by the incumbents. One of the bold responses to answer the disruptive era is by acquiring the new entrants to gain technology benefit and expanding the market. PT. X has the opportunity to develop their digital platforms and strengthen their digital capabilities through its subsidiary; PT. XYZ, a corporate venture capital which invest in many digital companies to pursue not only financial gain but also strategic objective that could support PT. X digitalization plan and give added value. When it comes to the startup exit strategy, the option of acquisition becomes important to preserve the added value from the strategic partnership. Therefore, further assessment is important to conduct in order to know which digital companies should be considered for acquisition due to its added value. The beginning of the research starts from identifying which partnerships are still lived up until 2019 then identifying the FCF or the added value that PT. X’s subsidiaries capture from the partnership with the digital companies. Later on, building the growth assumption for each partnership. To determine which digital companies should be considered for acquisition, Discounted Cash Flow (DCF) model is used in calculating the total added value until perpetuity which has been discounted using WACC of PT. X. Also, sensitivity analysis is constructed to identify the risk. According to the result, the total added value that PT. X gathered from the partnership with digital companies is Rp13.65 trillion dominated by Digital Company B, Digital Company E, and Digital Company C with the proportion of 67.41%, 18.60%, and 9.96% respectively. The researcher suggests that for long-term period PT. X is recommended to consider those digital companies for acquisition and do further assessment on assets valuation of those digital companies prior to acquisition. In a short-term period, maintaining the partnership with those digital companies is desirable. In addition, based on sensitivity analysis, the total value is very sensitive towards WACC changes. Therefore, PT. X should perform optimal capital structure to get maximum total value by reducing the WACC. Keywords: Digital Transformation, Corporate Venture Capital, Digital Company, Partnership, Added Value